Retropubic mid‐urethral slings and de novo urinary urgency and frequency: The role of retropubic hematomas. Issue 6 (30th June 2021) - Wu, Emily; High, Rachel; Lewis, Christopher; Kuehl, Thomas J.; Danford, Jill M.; Yandell, Paul M.
Abstract: Aims: This is a prospective cohort study comparing de novo lower urinary tract symptoms (LUTS) in subjects undergoing a retropubic mid‐urethral sling who either did or did not develop a postoperative retropubic hematoma within 6 weeks of surgery. The secondary objective was to measure the incidence and prevalence of retropubic hematomas, and subject characteristics associated with retropubic hematomas. Methods: Eligible subjects were recruited before undergoing a retropubic mid‐urethral sling with or without concurrent pelvic reconstructive surgery. Validated urinary symptom questionnaires were completed before surgery and at 6 weeks postoperatively. An abdominal ultrasound was used to establish baseline lower urinary tract imaging. Ultrasound was repeated immediately after surgery and 6 weeks later to assess for the presence of retropubic hematomas. Results: Ninety‐four subjects were enrolled. Baseline urgency and frequency were measured in 35% (33/93) of subjects. At 6 weeks postoperatively, 2% (1/52) had de novo LUTS which were not associated with a retropubic hematoma at any time. Immediately after surgery, the incidence of retropubic hematomas was 17% (16/94) while the prevalence of retropubic hematomas 6 weeks after surgery was 4% (3/75). There was no significant difference in the change in hemoglobin before and after surgery between those with and without postoperative retropubic hematomas. Conclusions: There is no significant association with de novo LUTS and retropubic hematomas. Though there is a 17% incidence of retropubic hematomas detected immediately after surgery, those with hematomas who were not lost to follow‐up resolved by the 6‐week postoperative visit and is of unclear clinical significance.